ANALISIS SENSITIVITAS di PT AE - Klinton Butar-Butar; Juanita R. Horman (INTAN Jurnal Penelitian Tambang, 2021)
PT. AE is engaged in the mining industry which in all its business activities requires a large investment. Therefore, it is necessary to conduct an investment analysis to see how the feasibility of this business using Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate Of Return (IRR) methods. Followed by sensitivity analysis to look at the company's financial condition in case of changes of ±2.50%, ±5.00%, and ±7.50% in revenue and cost of revenue. The results of the calculation of business feasibility analysis obtained a value of $618,450.563, BCR worth 1.698, and IRR worth 35.71%. This indicates that the efforts undertaken are worth carrying out. AE is more sensitive to -5.00% revenue-generating negative NPV, i.e. ($121,203.568), BCR at 0.881, and IRR of 2.69%. While the increase of cost of revenue was 7.50%, resulting in a negative NPV of ($178,160.513), BCR of 0.830, and IRR of -0.09%.